The Ahl al-Kitâb Conception in Islam: Dialogue with Religious Pluralism Proponents [مفهوم أهل الكتاب في الإسلام: الحوار مع أنصار التعددية الدينية] - Harda Armayanto (Karsa: Journal of Social and Islamic Culture, 2017)
The discussion about Ahl al-Kitâb enters into the study of religious pluralism. According to the supporters of this understanding, Ahl al-Kitâb consists of all religious people who have the holy book. So, all religious people can be mentioned as Ahl al-Kitâb. This opinion differs from classic commentators in Islam. Al-Thabari argued that Ahl al-Kitâb are only Jews and Christians. Moreover, Imam al-Shafi'i’s terminology was tighter, that Ahl al-Kitâb are only Jews and Christians from the descendants of Israel. This discussion is important because the criteria of Ahl al-Kitâb is related to the concept of salvation that exists in religions. For that reason, this article is going to place the meaning of Ahl al-Kitâb referring to the Qur'an and the Prophet's tradition. The writing of this article refers to the books of classical Muslim (turâts) as well as the works of contemporary authors who carry the notion of religious pluralism. Then, writer compares and concludes the Islamic teachings of the People of the Book. It is known that the People of the Book are Jews and Christians, not the others. Copyright (c) 2017 by KARSA. All right reserved DOI: 10.19105/karsa.v25i1.1247